The Effect of Institutional Ownership, Profitability, and Liquidity on Capital Structure with the Cost of Capital as a Mediating Variable: Empirical Study on Property Companies Listed on the Indonesia Stock Exchange 2018 - 2022 - Saumi Zulviana; Rida Prihatni; Etty Gurendrawari (Riviera Publishing, 2024)
This study aimed to determine and analyze the effect of institutional ownership, profitability, and Liquidity on capital structure with the cost of Capital as a mediating variable in property companies listed on the Indonesian stock exchange in 2018 - 2022. The method used in this research is quantitative. The population in the study were 92 Property and Real Estate companies listed on the Indonesia Stock Exchange in 2018-2022. The sampling technique used purposive sampling. The data analysis technique uses the classic assumption test and hypothesis testing. The results showed that in property companies on the IDX for the 2018-2022 period, institutional ownership had no significant effect on the structure and cost of Capital. Profitability has a significant negative effect on capital structure and a significant positive effect on the cost of Capital. Liquidity has no significant effect on capital structure, but is significantly negative on the cost of Capital. The cost of Capital has a significant positive effect on capital structure. It can mediate the effect of profitability on capital structure. However, it does not mediate the effect of institutional ownership and Liquidity. This study has implications for corporate financial policy, especially in managing capital structure and cost of Capital. Companies need to pay attention to profitability and liquidity factors in making financial decisions, because both significantly influence the structure and cost of Capital.